A dynamic subgrid-scale modeling framework for Boussinesq turbulence. (May 2017) - Maulik, Romit; San, Omer
Highlights: A dynamic model based on the approximate deconvolution is proposed for Boussinesq turbulence. The robustness of the model has been tested by considering the Rayleigh-Bénard turbulent thermal convection problem. It is shown that the proposed model could be a viable tool for subgrid-scale parameterizations in Boussinesq flows. Abstract: A modular dynamic subgrid-scale modeling framework is presented for large eddy simulation of two-dimensional Boussinesq turbulence. The procedure we put forth in this study allows us to couple the structural subgrid-scale parameterization models with the functional models by minimizing the error between them. In particular, the approximate deconvolution procedure is used to estimate the Smagorinsky and Baldwin-Lomax eddy viscosity constants and the associated turbulent Prandtl numbers self-adaptively from the resolved flow quantities. Our numerical assessments for solving the Rayleigh-Bénard turbulent thermal convection problem show that the proposed approach could be used as a viable tool to address the turbulence closure problem for the Boussinesq setting due to its accuracy and flexibility.